The Implementation of Aptitude Treatment Interaction (ATI) to Improve Learning Motivation of Low Achievement Students - Syawal, Syawal -; Hakim, Patahuddin -; Alimuddin, Alimuddin - (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This research was classroom action research, which aims at improving students motivation of their poor performance through learning model Aptitude Treatment Interaction (ATI) on VII.3 grade students of SMP Negeri 6 Parepare. Aptitude Treatment Interaction (ATI) can serve individual student differences by adjusting treatment or learning method with students abilities. The use of this model was emphasizing to create small groups of students that have achievement alike. Students with have low academic achievement based on test results and teacher interview will be grouped into one group and will be given preferential treatment by tutoring intensity rather than the group of high academic achievement. Subjects of this research were students of class VII.3 SMP Negeri 6 Parepare which is consist of 25 students. This research was conducted in two cycles. The procedure of this research involved four phases: (1) planning, (2) Implementation of action, (3) observation, (4) Reflection. The data collection was done by observation, tests, and questionnaires for each cycle after giving treatment through learning model Aptitude Treatment Interaction (ATI). Data collected were analyzed using quantitative and qualitative analysis. The results of this research indicate that the Aptitude Treatment Interaction (ATI) can be an alternative method to improve learning motivation of low achievement students. The results of this research also showed that the Aptitude Treatment Interaction (ATI) can be an alternative to problem-solving in the classroom, especially for low achievement students.